The revisioners ebook A novel. - Wilkerson Sexton, Margaret (2019)
This New York Times Book Review Notable Book of the Year from the author of the Reese Witherspoon Book Club pick, On the Rooftop , is "a powerful tale of racial tensions across generations" ( People ) that explores the depths of women’s relationships—influential women and marginalized women, healers, and survivors. In 1924, Josephine is the proud owner of a thriving farm. As a child, she channeled otherworldly power to free herself from slavery. Now her new neighbor, a white woman named Charlotte, seeks her company, and an uneasy friendship grows between them. But Charlotte has also sought solace in the Ku Klux Klan, a relationship that jeopardizes Josephine’s family. Nearly one hundred years later, Josephine’s descendant, Ava, is a single mother who has just lost her job. She moves in with her white grandmother, Martha, a wealthy but lonely woman who pays Ava to be her companion. But Martha’s behavior soon becomes erratic, then threatening, and Ava must escape before her story and Josephine’s converge. The Revisioners explores the depths of women’s relationships—powerful women and marginalized women, healers and survivors. It is a novel about the bonds between mothers and their children, the dangers that upend those bonds. At its core, The Revisioners ponders generational legacies, the endurance of hope, and the undying promise of freedom. "[A] stunning new novel . . . Sexton’s writing is clear and uncluttered, the dialogue authentic, with all the cadences of real speech . . . This is a novel about the women, the mothers." ― The New York Times Book Review